Nitrification-denitrification Process in a Combined AVFF and UAHFF System for Ammonia Removal - W ABD RAHMAN, WAN NUR AZLIN; R. HAMDAN, (Recent Trends in Civil Engineering and Built Environment, 2021)
High ammonia in the water body will accelerate the growth of aquatic plants as well as eutrophication in the water ecosystem. Domestic wastewater among the culprits of ammonia discharge due to the capability of an existing conventional wastewater treatment system which often unable to remove completely ammonia as mainly will be removed in tertiary treatment.  However, tertiary treatment requires a complex chemical process. Therefore, the main objective of this study is to develop an alternative treatment for enhanced ammonia removal from domestic wastewater. A lab-scale L-shaped semi-aerated with the combination of Aerated Vertical Flow Filter AVFF and Unaerated Horizontal Flow Filter UAHFF was mainly designed to study the nitrification-denitrification process in an aerated vertical and unaerated horizontal filter, respectively. The L-shaped semi-aerated filter was constructed with steel slag as a filter medium in the MPRC laboratory and the wastewater sample was collected from the influents of the UTHM Sewage Treatment Plant. The influent and effluent samples of wastewater were analyzed for pH, Dissolved Oxygen, turbidity, and nitrate twice a week for 3 weeks. Results from this study show that the effluent of the system was alkaline with a pH value range from (7.64 to 9.41) due to the nature of steel slag which is an alkaline media. Turbidity has been successfully removed as the percentage removal range from (75% to 89%). From the observation, the nitrification process taking place in the highly oxygenated AVFF system due to the increased nitrate concentration in the filter effluent whilst denitrification does not occur as the nitrate concentration remains high in the UAHFF effluent. This condition might be due to the reason that the UAHFF do not completely anoxic as the DO remain high, range from (4.87mg/L to 8.18mg/L). In conclusion, the system will be redesigned to enhance the denitrification process.